Analysis of possible negative effects of the prospects for the return of foreign companies in the Russian civil aviation industry ("Journal "U". Economy. Management. Finance.", 2025)
For more than 20 years, foreign companies have had a tremendous level of influence in the Russian civil aviation industry. There was literally not a single project where there was no obvious dependence on foreign companies. This was reflected not only in the supply of individual aircraft components, but also, most importantly, in the total share of aircraft in Russian avia companies’ fleets. This dependence has led to the fact that after the introduction of the first serious sanctions, the production of all Russian new civilian aircraft has been threatened. At the cost of great efforts and active work on import substitution, the Russian aviation industry managed to stabilize the situation and create a base for further growth. However, with possible improvements in international relations, the potential return of foreign companies may offset all the successes achieved. In these circumstances, it is necessary to understand the current role of foreign companies in Russia in the civil aviation industry, and how their return may affect the entire industry.
Keywords: foreign companies; civil aviation; civil aviation industry; import substitution; comprehensive industry development program until 2030; Boeing; Airbus